Time‐varying non‐line‐of‐sight (NLOS) satellite navigation channel modelling and simulation using multiple point‐scatterers - Shun Zhou; Gang Ou; Xiaomei Tang; Weihua Mou (IET Radar, Sonar & Navigation, 2022)
Abstract Recently, there has been an increasing interest in modelling and simulation of time‐varying (TV) non‐line‐of‐sight (NLOS) channels for global navigation satellite systems (GNSS) as an assisted means of resolving the GNSS urban canyon problem. In the above context, modelling and simulation of TV NLOS channels for GNSS have been investigated and studied due to their rapidly TV characteristics. However, conventional simulation approaches for TV multipath channels suffer from inconsistency and lack physical soundness, resulting in a non‐smooth transition of the Doppler shift and low simulation output accuracy. The authors propose an improved satellite navigation channel modelling and simulation method for TV NLOS reception scenarios. The multiple‐point‐scatterer model framework is applied to the TV NLOS satellite navigation channel model. The major novelty of the proposed method is integrating the multiple‐point‐scatterer model with online planning of a kinematics trajectory to map changes in the continuous velocity to the Doppler shift, which can keep consistency and accuracy. As a side benefit of the authors' work, numerical integration based on the efficient composite trapezoidal rule is proposed to calculate the precise changes in signal path length, phase, and Doppler shift. The numerical simulation results show that the proposed modelling and simulation method can not only accurately simulate the TV characteristics of the channel multipath with the continuous phase and the Doppler shift, but also reproduce the Rayleigh fading statistics of the TV channel, thus effectively approximating the physical propagation model and generating the TV NLOS satellite navigation channel.